Global Practices of Naturopathy - Tokika Yepthomi; Sangeeth Somanadhapai (Medical Research and Its Applications Vol. 1, 2024)
The foundation of Naturopathy or Naturopathic Medicine is based on the theories of health and disease, philosophical concepts, principles guiding assessment and various other treatments. Naturopathy or Naturopathic Medicine is a medical system that has evolved from a combination of traditional practices and healthcare approaches which popular in Europe during the 19th century. Naturopathic clinical education around the globe comprises a wide range of mostly non-drug-based treatments including lifestyle modification with counselling and psychological support, hydrotherapy, Chinese medicine and acupuncture, therapeutic massage, clinical nutrition and dietic, herbal medicine, homeopathy, intravenous and chelation therapy, environment medicine, mind-body medicine, physical medicine, ultrasound, diathermy, over-the-counter and prescription drug therapies or minor surgical interventions.